Statistical Analysis of Consequences Caused by the Collisions of Soaring Drops of Organic Coal-Water Fuel; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Valiullin T. R. Timur Radisovich (2017, 2017)
Title screen